Vitreous haemorrhage: a consequence of herpes simplex acute retinal necrosis - Sherina Quay,; Rosiah M,; Mushawiahti Mustapha, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Acute retinal necrosis (ARN) is a rare, blinding disease that typically affects adults. However, in this case report, we highlight the diagnosis, management and outcome of herpes simplex acute retinal necrosis in a 13-year-old healthy girl, who presented with painful right eye, redness and blurring of vision for one week. Examination of the right eye showed features of granulomatous panuveitis. Optic disc was swollen and retina appeared pale. There were multiple patches of retinitis and haemorrhages at mid-periphery of the fundus with inferior serous detachment observed. Rapidly progressive inflammation in just four days along with secondary cataract that obscured fundus view, imposed greater challenge to the diagnosis and management. Intravenous acyclovir 300mg, 3 times a day was initiated promptly while vitreous fluid was sent for polymerase chain reaction, which identified Herpes Simplex Virus-1. Inflammation improved, but she developed vitreous haemorrhage secondary to proliferative retinopathy, which required panretinal photocoagulation. ARN is therefore, principally a clinical diagnosis and high index of suspicion is crucial particularly, in children for prompt diagnosis and treatment. Complications should also be addressed timely to improve the chances of preserving vision.